Penghakiman oleh Pers Nasional: Suatu Kritik atas Kebebasan Pers dalam Pemberitaan Perkara Tindak Pidana Korupsi - Prahassacitta, Vidya (Humaniora, 2014)
The 1998 reform in Indonesia has changed freedom press in Indonesia. Now press implements libertarian model which puts freedom first instead of responsibility. Previously, press implemented soviet communist model which put responsibility first instead of freedom. Fifteen years later, press in Indonesia has become political tool by the owner of the press company who has high position in political party participating in the 2014 election. This reflects on the disproportional news regarding corruption cases conducted by the government officer or parliament member from the contender party. Such news delivers not only facts but also misleading opinions to the society which creates trial by the press. In fact, presumption of innocent principle is a foundation for press reporting news as stipulated in Law No. 40 Year 1999 concerning Press and Journalistic Code of Conduct. In libertarian press there are always borders but such borders are not effective since the freedom of press in Indonesia is powerful. Article used qualitative and library research with secondary sources of law to gain a solution to this problem. Therefore, Press Board should maximize its function in supervising the implementation of presumption of innocent principle and to raise society awareness regarding the law supremacy. In the end, to fulfill press social responsibility, a press profession court shall be established to keep press independency.